Pro-Phe Derivatives as Organocatalysts in Asymmetric Aldol Reaction - Karaoglu, Merve; Aydogan, Feray; Yolacan, Cigdem (BENTHAM SCIENCE PUBL LTD, 2021)
The aldol reaction which is the most important one among the C-C bond forming reactions, is widely used by synthetic organic chemists to obtain beta-hydroxycarbonyl compounds which are important starting components for biologically active compounds in optically pure form. In this research, five Pro-Phe derivatives were synthesized by simple amidation reactions and characterized by their spectral data. Their catalytic activities in asymmetric aldol reaction were investigated. The catalytic activity studies were performed with aliphatic ketones and various aromatic aldehydes. Especially, (S)methyl 3-mercapto-2-(S)-3-phenyl-2-((S)-pyrrolidine-2-carboxamido)propanamido)propanoate showed good catalytic activities in water at 0 degrees C in the presence of p-nitrobenzoic acid cocatalyst. The enantioselectivities were up to 90.4%, the diastereomeric ratios were up to 97/3 and yields were 99%. The results showed that these organocatalysts were promising organocatalysts for aldol reaction. Besides, this catalyst showed its best catalytic activities in water which is also an important contribution to green chemistry requirements.
Keywords: Pro-Phe derivatives; Aldol reaction; Organocatalysis; Asymmetric synthesis; Proline; Water solvent; AQUEOUS-MEDIA; SOLVENT; DIPEPTIDES; CATALYSTS; ACETONE; WATER; Chemistry